The rise and fall of central dogmas. (2nd October 2016) - Klein, George; Klein, Eva
ABSTRACT: Stimulated by Francis Cricks "central dogma of molecular biology" open to criticism and rebuttal, five statements are formulated on current notions of tumor biology, inviting the criticism of the reader.